Diversity and use of non-conventional food plants in quilombola communities in northeast Brazil - Jociene Oliveira Vitória Nascimento; Bruna Farias de Santana; Eraldo Medeiros Costa Neto; Robert A. Voeks; Ligia Silveira Funch (Acta Botânica Brasílica)
Abstract Studies on the cultural importance of unconventional food plants (UFP) have been scarce, in contrast to a vast literature focusing on medicinal plants. We adopted the widely used criterion of cultural importance to study UFP used in two quilombola communities in Bahia State, northeastern Brazil. Free-listing was applied to identify known/used food plants in the communities, and semi-structured interviews were carried out to collect information about them. Statistical analyses were performed using a correlation matrix of importance values. A random sample of the numbers of citations per species indicated a strong correlation between cultivated and wild species. The average ages of the two communities were similar, but indicated an influence of age on their knowledge of non-conventional plants and their consumption. Both wild and cultivated species have relevant cultural importance. Deforestation, the lack of availability of unconventional food plants, and the ease of access to conventional and industrialized foods are all directly related to the low consumption of UFP, pointing to a lack of nutritional and health information in those communities.